Leveraging of digital triage to enhance access in obstetric emergencies in the maternity units: A scoping review of digital triage interventions in healthcare - Mxolisi Welcome Ngwenya; Livhuwani Muthelo; Mellitah Molatelo Rasweswe; Tebogo Maria Mothiba (Digital Health)
Background Pregnancy and childbirth are supposed to give a new beautiful meaning to life and it is a time of enormous delight and anticipation for both the women and their families. In these times, not only a baby is born, but a mother is born. However, inaccessibility and delays in obstetric care remain a common concern, particularly in low- and middle-income countries. Digital health technologies are being implemented to improve healthcare access worldwide, but there is a lack of documented data on available digital triage interventions. This article sought to examine and critique existing digital triage interventions in the healthcare system with reference to obstetrics. Methods Adopting a scoping review approach, using the five iterative steps proposed by Arksey and O'Malley, approximately 17 studies retrieved from databases like PubMed, Elsevier, EBSCohost, and google scholar were reviewed. Only the literature from 2014–2024 was included. Results The review revealed that there are various types of digital triage interventions. However, they are flooded with weaknesses and threats among of which are diagnosis inaccuracy, insufficient information, and shortage of resources. Conclusions The study recommends that strengths, weaknesses, opportunities, and threats should not be overlooked, particularly when aiming to leverage digital health to improve access to emergency care in maternity units through digital triage. However, they should serve as a reference for the development of optimal digital triage systems for maternity and emergency units. Furthermore, the findings should also be a benchmark for digital triaging improvement strategies in the healthcare context.